End‐of‐life care of oncology inpatients: Are we getting it right?. Issue 5 (13th June 2018) - Batten, Monique; Nguyen, Bella; Burke, Brandon; Harryanto, Hilman; Mitchell, Imogen; Davis, Alison
Abstract: Aim: To examine the current patterns of end‐of‐life care of medical oncology patients dying in an Australian tertiary acute hospital setting in order to determine potential areas for improvement. Methods: A retrospective observational study was undertaken of 295 consecutive adult medical oncology inpatients dying between 2010 and 2015. Charts were reviewed for evidence of (1) resuscitation plans, (2) acute interventions in the 48‐h period prior to death, (3) palliative care involvement and (4) recognition of the dying patient and comfort care plans. Results: At the time of death, 98% of patients had a resuscitation plan, 71% of which were completed by the medical oncology team. Fifty‐nine percent of medical emergency team reviews occurred in patients without a documented resuscitation plan. Within 48 h of death, active interventions were still being given to 64% of patients in the total patient population. Comfort care plans were documented in 86% of patients; however, 62% of these were only documented within 48 h of death and 20% of patients with a documented comfort care plan still received noncomfort measures. Conclusion: There was a high level of documented resuscitation plans, comfort care plans and recognition of dying. However, active interventions were common within 48 h of death, and comfort care plans and recognition of dying often occurred late. These data indicate a gap between documenting a resuscitation plan and providing timely and appropriate end‐of‐life care. Understanding the gaps in delivering appropriate care provides an opportunity for improving end‐of‐life care.